Antioxidant and cardioprotective effect of a polyherbal Formulation against isoprenaline hydrochloride induced Myocardial necrosis in rats - P.KAVITHA; C. SOWMIA (International Journal of Pharma and Bio Sciences, 2017)
The present study was designed to evaluate the effect of Polyherbal formulation (250 mg/kg and 500 mg/kg body weight) on Isoprenaline hydrochloride induced myocardial necrosis in experimental rats. The herbal formulation that was prepared has synergistic effect and will reduce the toxicity of individual herbs. Isoprenaline hydrochloride (IPH) induced myocardial infarction was confirmed by disturbances in marker enzymes such as ALT, AST, LDH, CK and CK-MB. The increased in oxidative stress was evidenced by a significant (P<0.05) decline in LPO, enzymatic and non-enzymatic antioxidants (SOD, CAT, GPx, Vitamin C, and Vitamin E) in the heart tissue. Polyherbal formulation (PHF) treated rats displayed a significant (P<0.05) increase in the levels of these parameters when compared to normal and standard drug pretreated groups. From the results the PHF (500 mg/kg body weight) showed a significant cardioprotection against IPH induced cardio toxicity in rats, by significantly decreasing the cardiac enzymes as well as increasing the enzymatic and non-enzymatic antioxidants.